2006
DOI: 10.1002/cncr.21734
|View full text |Cite
|
Sign up to set email alerts
|

Cellular features of endometrial hyperplasia and well differentiated adenocarcinoma using the Endocyte sampler

Abstract: If a large amount of polymer radicals remain trapped after the irradiation of ultrahigh molecular weight polyethylene (UHMWPE), the radicals may result in a significant alteration of its physical properties during long‐term shelf storage and implantation. An electron spin resonance spectroscopic study was undertaken to investigate the remaining free radicals in UHMWPE after electron beam irradiation up to 500 kGy in air and an N2 environment. Heat treatment was employed at 110 and 145°C for various periods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 114 publications
(175 reference statements)
6
92
0
3
Order By: Relevance
“…In our current study, we found that EH with atypia (AEH) consists essentially of two cellular patterns: glands with a dilated or branched pattern and glands with an irregular protrusion [6,9]. However, no correlation between these cytologic and histologic categories appeared to exist, although we described a continuum of changes from atypical to carcinoma.…”
Section: Cellular Findings In Ehmentioning
confidence: 74%
See 2 more Smart Citations
“…In our current study, we found that EH with atypia (AEH) consists essentially of two cellular patterns: glands with a dilated or branched pattern and glands with an irregular protrusion [6,9]. However, no correlation between these cytologic and histologic categories appeared to exist, although we described a continuum of changes from atypical to carcinoma.…”
Section: Cellular Findings In Ehmentioning
confidence: 74%
“…In a paper by Coscia-Porrazzi [27], benign complex hyperplasia was characterized by branching glandular structures comparable to those we have observed in the current study. From the cytologic point of view, we believe that the recognition of glands with a dilated or branched pattern is a useful feature in EH [6,7]. The basic cellular features of glandular epithelium (apart from the overall architecture) resemble those of PE glands in normal endometrium; the cytoplasm is commonly scant and the nuclei are isomorphic with finely granular chromatin and small or absent nucleoli.…”
Section: Cellular Findings In Ehmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that, at times even when curettage findings have been normal, endometrial aspiration cytology has been found to be useful for diagnosing endometrial pathology. [8] Outpatient sampling of the Endometrium could complement conventional curettage and assist in patient management.…”
Section: Discussionmentioning
confidence: 99%
“…In Endometrial hyperplasia, cell aggregates with a dilated or branched pattern were found in 34.9% of cases. [8] The cytological differentiation between atypical hyperplasia and endometrial adenocarcinoma was another difficulty that we faced. This issue was discussed in two sessions at the XV International Congress of Cytology, (Santiago de Chile, 2004), 'The Jiménez-Ayala Classification' was proposed by Jiménez-Ayala M which divided endometrial proliferative lesions as endometrial hyperplasia and endometrial neoplasia.…”
Section: Discussionmentioning
confidence: 99%